Comparative osteology of Tor tambroides (Bleeker, 1854) and Tor tambra (Valenciennes 1842) vertebral column (ossa vertebrae) - Yusrizal Akmal; Muhammad Radhi; Muslich Hidayat; Muliari Muliari; Ilham Zulfahmi (Jurnal Iktiologi Indonesia, 2020)
Information related to osteology plays a vital role in support ecomorphology and phylogenetic relationship analysis in fish. This study aimed to describe the comparative morphology of the vertebral column between Tor tambroides (Bleeker, 1854) and Tor tambra (Valenciennes 1842). Samples of Tor tambroides and Tor tambra were obtained from fish traders in the Tangse River area of Pidie Regency and Sampoinet River area, Aceh Jaya Regency, Aceh Province. Vertebral column preparation consists of five steps: muscles and scales separation, immersion in a formaldehyde solution, drying, morphometric measurements, photographing and image editing, and identification of terminology. The results showed that there are morphological differences between Tor tambroides and Tor tambra vertebral column, particularly in the axial vertebrae, posterior vertebrae caudales, and urostylus regions. The pleural costae of Tor tambroides have a posterior curve with the left and right sides interlocking. The lateral Tor tambroides process tends to curve posteriorly, while the Tor tambra tends to round up parallel to the dorsal costae. Tor tambroides tend to have stronger ligaments marked by the absence of a foramen between the hypural. Morphometrically, Tor tambroides tend to have higher centrum ratios (length, width, and height), neural spine, haemalis spine, and costae compared to Tor tambra. The significant difference in morphometric results in observed the axial vertebrae and the posterior vertebrae caudales region. Further research related to the correlation of vertebral column morphology with the environmental condition of these fish is still necessary. Abstrak Kajian osteologi memiliki peran penting dalam upaya analisis ekomorfologi dan hubungan filogenetik antarjenis ikan. Penelitian ini bertujuan untuk mendeskrispsikan perbedaan morfologi tulang belakang Tor tambroides (Bleeker, 1854) dan Tor tambra (Valenciennes 1842). Contoh ikan Tor tambroides dan Tor tambra dikoleksi dari hasil tangkapan nelayan di wilayah Sungai Tangse Kabupaten Pidie dan wilayah Sungai Sampoinet, Kabupaten Aceh Jaya, Provinsi Aceh. Tahapan preparasi tulang belakang terdiri atas lima tahapan yaitu pemisahan otot dan sisik, perendaman dalam larutan formalin, penjemuran, pengukuran morfometrik, pemotretan dan penyuntingan gambar, serta identifikasi terminologi. Hasil penelitian ini menunjukkkan bahwa terdapat perbedaan morfologi tulang belakang antara Tor tambroides dan Tor tambra terutama pada bagian axial vertebrae, posterior vertebrae caudales dan urostylus. Tulang pleura costae Tor tambroides memiliki bentuk melengkung ke arah posterior dengan bagian kiri dan kanan saling bertautan. Processus lateralis Tor tambroides cenderung melengkung ke arah posterior, sedangkan pada Tor tambra cenderung membulat sejajar dengan dorsal costae. Tor tambroides cenderung memiliki ligamen yang lebih kokoh ditandai dengan tidak adanya foramen diantara os hypural. Secara morfometrik tulang belakang, Tor tambroides cenderung memiliki nilai nisbah centrum (panjang, lebar dan tinggi), spina neuralis, spina haemalis dan costae yang lebih tinggi dibandingkan dengan Tor tambra. Disparitas hasil pengukuran antara kedua jenis ikan terlihat cukup kentara pada bagian axial vertebrae dan bagian posterior vertebrae caudales. Penelitian lanjutan terkait korelasi morfologi tulang belakang dengan kondisi perairan kedua jenis ikan masih perlu dilakukan.